STUDIUM PUNCTUM: POLITIK CITRA PUTIN DALAM FOTO САММИТ СТРАН БРИКС 2024 / SAMMIT STRAN BRIKS (KTT BRICS 2024) - Wahyuningsih, Dyah Hayu Permatasari; Limbong, Banggas (UI Scholars Hub, 2025)
This research takes a data corpus in the form of visuals provided by five Russian digital news channels with a focus on the image of Vladimir Putin as the leader of Russia at the BRICS Summit congress in Kazan in 2024. The author will analyze five online news channels from Russia published between October 23, 2024 and October 25, 2024 with headlines related to the 16th BRICS Summit in Kazan. The method used in this research is a descriptive analysis method. Through this research, the author will explain the meaning contained in the visualization of these online news as a medium to convey a meaning. Behind the image is certainly a propaganda technique that shows the way the current Russian leader, Vladimir Putin, leads the new world order through the BRICS organization. From the results of the research it can be concluded that behind the visualizations included as research topics there is meaning and how the use of images in the news as a tool for shaping perceptions that can form public opinion and convey ideological messages.